P1 Omalizumab in Paediatric Asthma: Importance of Multi-Disciplinary Assessment to Identify Eligible Patients. (19th November 2012) - Rao, S; Barrett, L; Frost, S
Abstract : Omalizumab is effective treatment for patients with severe asthma. It is reserved for patients with truly severe disease as it is expensive and associated with significant treatment burden. Identifying this small number of patients in problematic severe asthma (PSA) group is challenging. We evaluated the impact of multi-disciplinary severe asthma (SA) protocol on identifying those with severe disease and on potential use of omalizumab. After initial clinic visit, 19 patients aged between 6–15yrs with PSA underwent specialist nurse led SA protocol which included: assessment of clinical status, lung function, atopy, inhaler technique, asthma control test (ACT), quality of life (QoL); home visit for further assessment of environment, adherence and psychosocial comorbidities; school contact to address impact on education. Before SA protocol, 17/19 patients met criteria for use of omalizumab. After SA protocol, only 6(35%)were eligible as modifiable factors were identified in 11(65%). They included poor adherence, ongoing allergen exposure and psychological issues. 5/6 patients received omalizumab and 4(80%) improved. Of other 11 patients, clinical status improved in 6 (55%), unchanged but stable in 4(36%), worsened in 1(9%) after assessment. SA protocol identified modifiable factors in significant proportion of PSA children limiting omalizumab use to those with truly severe disease. Home visit assessment is essential to identify these factors which would otherwise be unrecognised. We hypothesise that proper recognition and management of these factors might not only ensure appropriate use of omalizumab but also improve its effectiveness.